Pooled testing for SARS‐CoV‐2 infection in an automated high‐throughput platform. Issue 7 (28th June 2021) - Dash, Girish Chandra; Rout, Usha Kiran; Nanda, Rashmi Ranjan; Parai, Debaprasad; Choudhary, Hari Ram; Kanungo, Srikanta; Palo, Subrata Kumar; Kshatri, Jaya Singh; Turuk, Jyotirmayee; Mishra, Bijaya Kumar; Pati, Sanghamitra; Bhattacharya, Debdutta
ABSTRACT: Background: Active detection of SARS‐CoV‐2 infection through testing is elementary for the control of COVID‐19 pandemic. The implementation of large‐scale RT‐PCR testing has led to a rise in the demand for testing kits whose availability is always a concern. Objective: To find out the feasibility of pooled testing in a high‐throughput platform. Methodology: Pooled testing was conducted in Roche cobas 6800 in 2 methods. Firstly, the simple two‐stage testing algorithm was conducted for 1410 samples individually and then as pooled samples. Secondly, we evaluated the sensitivity of cobas 6800 for the detection of a single positive sample within a pool of negative samples. Results: Implementing the five‐sample Dorfman pooling to test 1410 samples, we identified 42 (2.9%) individual SARS‐CoV‐2‐positive samples and 27 (9.5%) positive pool samples. The pooling strategy precisely identified all the positive samples. All individually negative samples were also accurately determined by pooling. There was 100% sensitivity of detecting positive samples in a pool of negative samples even up to 1:64 dilution. There was a threefold increase in total throughput in one‐third of the cost per day. Conclusion: A high‐throughput platform such as Cobas 6800 can effectively increase the testing capacity by twofold to threefold by adopting the pooled testing strategy for successful management of SARS‐CoV‐2 and helping in the containment of community transmission. Abstract : Five‐sample Dorfman pooling to test 1410 samples in Automated Cobas 6800 showed precise identification of all positive samples. There was 100% sensitivity of detecting positive samples in a pool of negative samples even up to 1:64 dilution. There was a threefold increase in total throughput in one‐third of the cost per day. If introduced effectively, pooling strategy would significantly help to reduce testing time, work, and reagents, enabling a substantial increase in productivity of clinical diagnostic laboratories and opening the door for the productive screening of large populations to detect the presence of SARS‐CoV‐2 infection.